THE CORRELATION BETWEEN VOCABULARY MASTERY AND WRITING SKILL OF SECONDARY SCHOOL STUDENTS - Hasan Hasan; Nanang Bagus Subekti (JELLT (Journal of English Language and Language Teaching), 2017)
The purposes of this study are to find out the score of students’ vocabulary mastery and writing descriptive text ability and also the correlation between students’ vocabulary mastery and writing descriptive text ability among the seventh grade students in SMP N 3 Bantul Yogyakarta academic year 2016/2017.This study used descriptive and correlational analysis. The data collection technique used were two tests, multiple choices test to find out the students’ score of vocabulary mastery and essay test to find out the score of students’ ability in writing descriptive text and to find out the correlation between students’ vocabulary mastery and writing descriptive text ability among the seventh grade students in SMP N 3 Bantul Yogyakarta in the academic year 2016/2017.The result of this study showed that students’ mean in vocabulary mastery was 67.12 greater than the ideal mean 53.5. The mean of students’ writing ability was 63.79 close to the ideal mean 70. Based on the result, it is shown that there is a positive and significant correlation between vocabulary mastery and writing descriptive text ability. It means that vocabulary mastery influences writing ability.